2017
DOI: 10.5830/cvja-2017-028
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of radiation safety training among interventionalists in South Africa

Abstract: SummaryExposure to ionising radiation may have deterministic and stochastic health effects, which include skin changes, chromosomal aberrations, cataracts and carcinomas. Formalised training in radiation safety and protection improves knowledge on the subject and facilitates greater compliance in safety practices. This qualitative study included 54 interventionalists (adult and paediatric cardiologists, and interventional radiologists). The participants were purposively selected and interviewed to explore thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…48 The training curriculum on radiation safety is inadequate for South African cardiologists and the gap in this training requires urgent attention. 49,50 The training needs to be included in the formal training curriculum and in the CME programme to ensure consistency in practice. 12 Training provokes improvement in the radiation management skills of operators, which improves the safety of all team members and patients in the catheterisation laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…48 The training curriculum on radiation safety is inadequate for South African cardiologists and the gap in this training requires urgent attention. 49,50 The training needs to be included in the formal training curriculum and in the CME programme to ensure consistency in practice. 12 Training provokes improvement in the radiation management skills of operators, which improves the safety of all team members and patients in the catheterisation laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…A South African study showed that there was a gap in the training on radiation safety in South African cardiologists. 25 Radiation safety training, however, also needs to be ongoing for it to be effective. 26 Adequate education on radiation safety mitigates the occupational risk of IR exposure to interventionalists working in the catheterisation laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…[6] It is important that different specialties employing radiation receive dedicated instruction and training in radiation safety to optimise their medical practice. [13] Most participants (95.4%) indicated that it was necessary to include radiation safety in the curriculum. Overall, participants indicated low levels of satisfaction (44.1%) with the level of radiation safety training they had received.…”
Section: Short Research Reportmentioning
confidence: 99%
“…The combination of these two factors should encourage the curriculum developers for these two groups to investigate and address this omission, especially for cardiology training. [13] One study indicated that implementation of a training programme resulted in a significant short-and long-term reduction in radiation dose to patients and radiation HCWs. [14] Advocating small behavioural changes among interventionalists reduces radiation during procedures, but requires educating them, especially cardiologists.…”
Section: Short Research Reportmentioning
confidence: 99%